(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The process of using the web platform on the basis of informatization of education increases the level of activity of the learner, grows alternative thinking skills, forms the skill of seeking solutions to the tasks set, allows you to develop the skills of computer modeling, algorithmic construction and programming of the objects and phenomena under study, and integrate the results of interaction between them.